Estudo sobre a desvalorização profissional a partir da discriminação salarial dos(as) assistentes sociais : análise de editais de instituições públicas em Sergipe (2011-2021) - Almeida, Leislayne Lima de (2022)
The present study has as its research object the professional devaluation of social workers from the wage discrimination existing in the hiring of Social Work professionals in different socio-occupational spaces. Part of the discussion around the insertion of social workers in the labor market, highlighting social and gender inequality. In this sense, this work calls into question the devaluation of the profession at the time that it is historically performed, mostly, by women. The motivation for the study was due to the observation of changes in the labor market, such as the presence of women in jobs that were not common to them and the different remuneration both in general and in relation to the remuneration assigned to professionals of Social Work, in different areas. Understanding the wage discrimination of the profession is a relevant theme to apprehend the sociohistorical determinations of Social Work as a profession with a dominant female character at the same time that it demarcates the gender inequality present in society based on the sexual division of work, imposed by capitalism and the patriarchy in order to make difficult in various ways the struggle for social and sexual equality, marked by advances and setbacks. Furthermore, the socioeconomic determinations present in the uneven and combined development of Brazilian capitalism also affect this context, which brings particularities to its social-historical formation. The general objective is to analyze the devaluation of the profession from the analysis of the wage discrimination of social workers present in the selective processes and public contests of the state of Sergipe, in the period from 2011 to 2021. Regarding methodology, historical-dialectical materialism supports the analysis of phenomena beyond their appearance, seeking to establish the associations that identify their essence. Quantitative-qualitative, bibliographic and documentary research is used, the latter having as main source the public notices for the opening of selective processes and public tenders, in Sergipe, in the period from 2011 to 2021, with vacancies for professionals with professional training in Social Work, in positions appointed or not as a social worker. Aspects such as the amount of salary offered in public tenders and selection processes, working hours and number of public tenders and selection processes in Sergipe were evaluated. Qualitative elements discussed include salaries offered to social workers. From the survey of the main documental source, the following results were found: of the total of 69 notices found, 50 refer to public tenders and 19 to selective processes; and of the 69 notices found, 57 of them were intended for certain municipalities in Sergipe and 12 for the occupation of functions allocated in the state of Sergipe, without specifying the municipality. In addition, 61.3% of the notices offered only one vacancy, 69.9% of the notices corresponded to a workload of 30 hours per week and 73.1% of the salaries offered were between one and two minimum wages, categorized according to the annual readjustments. In view of this, we observe that the profession experiences a clear process of social devaluation in the offer of jobs, whether temporary (selection processes) or effective (public tenders).